ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI WAKTU TUNGGU PENGADAAN MATERIAL BETON PADA BEBERAPA PROYEK DI JAKARTA - Oei Fuk Jin; Lolom Evalita Hutabarat; Andri (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2022)
This research is on the factors influencing the lead time of concrete material procurement in Jakarta. If the accurate material procurement lead time is getting longer, it can impact many losses on the project planning building. Factors that have been found from many studies of literature and field studies were analyzed by factor analysis and multiple linear regression analysis. Data was obtained by distributing a questionnaire to 30 respondents. After the data is retrieved and processed using factor analysis, ten variables are identified that influence the concrete material procurement lead time. These ten variables can be grouped into three major groups, namely, the cost factor, transportation factor, and internal factor. Then these ten variables were analyzed using multiple linear regression analysis by adding the dependent variable, i.e., the delay in procurement of the concrete material. The results of multiple linear regression analysis can be seen from the significant value. Four factors affect the independent variable. Four of the most influential are the number of staff, transport availability, material price increase, and fuel price increase. Knowing these factors is expected to reduce the risk of concrete material procurement lead time becoming longer.